A self-propelled hydraulic floor crane. - Sulaiman, Shamsuddin; Abdul Aziz, Faieza; Ahmad, Desa; Safarzadeh, Daryoush (2012)

(untitled)
The present invention relates to a self-propelled hydraulic floor crane comprising: a base frame including a column; a crane assembly coupled to the base frame; a hydraulic assembly for driving the movement of the crane assembly; a plurality of wheels coupled to the base frame; and characterized by; the crane assembly further including a plurality booms coupled to the column; a steering assembly coupled to the base frame and the plurality of wheels; wherein the plurality of booms and the steering assembly are driven by the hydraulic assembly; a driving assembly coupled to the plurality of wheels and driven by a motor; and a control unit for controlling the hydraulic assembly, the driving assembly and the steering assembly.